Profil Hormon Progesteron pada Anjing Kintamani Fase Anestrus Setelah Disuntik Pregnant Mare Serum Gonadotrophin (THE PROGESTERONE PROFILE IN ANESTRUS KINTAMANI BITCHES AFTER INJECTED USING PREGNANT MARE SERUM GONADOTROPIN) - Puja, I Ketut (Jurnal Veteriner, 2016)
Profil Hormon Progesteron pada Anjing Kintamani Fase Anestrus Setelah Disuntik Pregnant Mare Serum Gonadotrophin (THE PROGESTERONE PROFILE IN ANESTRUS KINTAMANI BITCHES AFTER INJECTED USING PREGNANT MARE SERUM GONADOTROPIN)
Keywords: PMSG; HSG; progesterone; Kintamani bitches